Investigating the effects of Brachiaria (Syn. Urochloa) varieties on soil properties and microbiome - Merloti, Luis Fernando; Bossolani, João William [UNESP]; Mendes, Lucas William; Rocha, Gabriel Silvestre; Rodrigues, Mayara; Asselta, Fernanda Ometto; Crusciol, Carlos Alexandre Costa [UNESP]; Tsai, Siu Mui (Springer Nature, 2023)
Background and aimsThe Brachiaria sp. (synonymous with Urochloa) is one of Brazil’s main grass species used in livestock production and has become the focus of breeding genetic programs to enhance its resistance to drought, flooding, and pests, as well as improving its palatability to animals. However, there is a limited understanding of how genetic breeding can affect the soil microbiome and its potential functions. Thus, this study aimed to investigate the impact of four different Brachiaria varieties on the soil prokaryotic and fungal communities, with focus on the N-cycle.MethodsWe combined molecular techniques, such as quantitative PCR and amplicon sequencing, to target prokaryotic and fungal communities and traditional soil and plant chemical analyses. The treatments were composed of the varieties of B. brizantha cv. Marandu (BM), B. ruziziensis (BR), Brachiaria spp. cv. Ipyporã (BI), B. brizantha cv. BRS Paiaguás (BP) and control without plants.ResultsOur findings revealed that all varieties improved soil porosity, P content, organic carbon, and potential functions as Chemoheterotroph, Aerobic-Chemoheterotroph, and Pathotroph-Saprotroph groups. Soil acidity, nutrient availability, and porosity were the main drivers of the microbial communities. The study also identified the ability of each variety to recruit microbial nitrogen-fixers and ammonia-oxidizers.ConclusionWe highlighted that Brachiaria varieties can favor soil microbial communities related to the release of nutrients, resistance to pathogens, and environmental stress. Also, the BI variety showed a higher potential to improve soil quality by increasing soil porosity and potential AMFs. Besides that, all varieties showed some potential to benefit intercropping and crop rotation systems.